1993
DOI: 10.1002/arch.940230203
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [3H]‐ecdysone in embryos and larvae of the tick Ornithodoros moubata

Abstract: The fate of [3H]-ecdysone ([3H]-E) was investigated in hanging drop cultures of embryos and larvae of the tick Ornithodoros moubata using HPLC. The hormone was metabolized more slowly during described periods of increasing endogenous ecdysteroid (ES) titers than during periods of low titers except for young embryos. Three different classes of metabolites were produced: 1) apolar products (AP) corresponding to C-22 fatty acid ester conjugates of E and, in some cases, of 20-hydroxyecdysone (20E), 2) unidentified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been reported that several nutritional factors can affect the process of moulting performance. Molting in crustaceans is triggered by ecdysteroid (Nakatsuji & Sonobe, ), which is metabolized in conjugation with eicosanoids (Dotson, Connat, & Diehl, ). Eicosanoids are main derived from LC‐PUFA such as ARA, EPA and DHA (Schlotz, Sørensen, & Martin‐Creuzburg, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several nutritional factors can affect the process of moulting performance. Molting in crustaceans is triggered by ecdysteroid (Nakatsuji & Sonobe, ), which is metabolized in conjugation with eicosanoids (Dotson, Connat, & Diehl, ). Eicosanoids are main derived from LC‐PUFA such as ARA, EPA and DHA (Schlotz, Sørensen, & Martin‐Creuzburg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Molting in crustaceans is regulated by ecdysteroids secreted from the Y‐organ, which is released into the haemolymph (Subramoniam 2000). It is shown that ecdysteroids get metabolized in conjugation with eicosanoids (Doston, Connat & Diehl 1993) to control the molting. This again can be related to the important role of 20:5n‐3 and 22:6n‐3 in accelerating the intermolt period and production of greater carapace widths in the first crab stage of S. serrata (Suprayudi et al 2004a) and Portunus trituberculates (Takeuchi, Satoh, Sekiya, Shimizu & Watanabe 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, embryos could metabolise [ 3 H]ecdysone in vitro into 22-fatty acyl esters, 20,26-dihydroxyecdysone (an intermediate in 26-oic acid formation) and 20hydroxyecdysone. Significantly, 20-hydroxylation first became evident in 2-day-old embryos, with highest activity occurring during increasing endogenous ecdysteroid titres (Dotson, Connat & Diehl, 1993). Although fatty acylation occurred in all stages, it was more pronounced during periods of low endogenous ecdysteroid titres.…”
Section: Embryogenesismentioning
confidence: 89%
“…Although fatty acylation occurred in all stages, it was more pronounced during periods of low endogenous ecdysteroid titres. It has been suggested that ecdysteroid fatty acyl ester may represent a detoxification mechanism in O. moubata eggs, although their true significance is uncertain (Dotson et al 1993).…”
Section: Embryogenesismentioning
confidence: 99%